2006
DOI: 10.1089/tmj.2006.12.639
|View full text |Cite
|
Sign up to set email alerts
|

Willingness-to-Pay Stated Preferences for Telemedicine Versus In-Person Visits in Patients with a History of Psoriasis or Melanoma

Abstract: The objective of this study was to evaluate willingness-to-pay stated preferences for telemedicine versus in-person clinic visits in patients with a history of psoriasis or melanoma. Face-to-face interviews were conducted with 92 (n = 92) adult participants with a history of psoriasis or melanoma recruited primarily from hospital-based dermatology practices. Data were collected on patient demographics and willingness-to-pay responses. In a combined analysis for patients with melanoma and psoriasis, 73% of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 13 publications
4
53
0
3
Order By: Relevance
“…23 Isolated reports of the use of online consultations have been disappointing. For example, despite indications that electronic communication could decrease health care costs 24 and provide reimbursement from patients, 25,26 Fairview Health System has reported only 10 e-visits per week in a system with 400 physicians, 27 and Blue Cross of Studies have not described a portal for online patient consultations that has a structured medical history. Structured computerized histories were first described in the 1960s by Mayne et al 28 and Slack et al 29 Their work included using the telephone and teletype with patients from distant locations providing their histories.…”
mentioning
confidence: 99%
“…23 Isolated reports of the use of online consultations have been disappointing. For example, despite indications that electronic communication could decrease health care costs 24 and provide reimbursement from patients, 25,26 Fairview Health System has reported only 10 e-visits per week in a system with 400 physicians, 27 and Blue Cross of Studies have not described a portal for online patient consultations that has a structured medical history. Structured computerized histories were first described in the 1960s by Mayne et al 28 and Slack et al 29 Their work included using the telephone and teletype with patients from distant locations providing their histories.…”
mentioning
confidence: 99%
“…Patients perceived digital health as an added value to their post-treatment care [15][16][17]20,25]. However, a majority of the studies reported the benefits of digital interventions to prevent recurrence and promote early detection [15][16]20].…”
Section: Principal Resultsmentioning
confidence: 99%
“…[15], a web-based platform (OIN TM ) to deliver information about melanoma [16], and store-and-forward tele-consultation [25]. The latter used a Willing-To-Pay (WTP) approach in order to investigate dermatology patients' preferences.…”
Section: Study Design and Interventionmentioning
confidence: 99%
See 2 more Smart Citations